Die naggesigte van Sagaria teen die agtergrond van konflik in die vroëë na-eksiliese gemeenskap in Juda - Bartlett, A. L. (Verbum et ecclesia, 1995)
The Night Visions of Zechariah against the background of conflict in the early postexilic community in Judah. In this article Paul D Hanson's view that the Night Visions of Zechariah should be interpreted against the background of a situation of conflict in post-exilic society is taken up. His description of the text as a hierocratic document aimed at the restoration of the pre-exilic status quo is however challenged. It is indicated that the Night Visions should rather be read as text purporting to inspire its readers towards involvement in the processes of change in society. Different levels of meaning, reflecting various aspects of the conflict in the community, can be indicated in the text.